Soil-water characteristic curves of hydrophobic sand - Tan, Nicole Shi Qi (Nanyang Technological University, 2022)
Soil hydrophobicity has been widely investigated as it appears naturally in many places and its effect is significant. In this project, the effect of hydrophobicity is investigated using fine and coarse sands. Fine sand was made hydrophobic and mixed with either fine or coarse sand such that sand mixtures of hydrophobicity 20%, 50% and 80% by mass were obtained. The Tempe cell was utilized to obtain the soil-water characteristic curves (SWCCs). The effect of hydrophobicity was shown to have a significant effect on the SWCC and the Fredlund and Xing (1994) equation was used to fit the SWCCs. Generally, as hydrophobicity increases, the Fredlund and Xing (1994) equation parameters ‘a’ and ‘n’ increase while ‘m’ decreases. Fine sand mixtures were shown to have higher air-entry values as compared to fine-coarse sand mixtures. Sessile drop tests were conducted to measure the apparent contact angles of the different mixtures to determine the degree of hydrophobicity of the sand mixtures. It was found that sand mixtures of 50% or more hydrophobicity show the same apparent contact angle implying that it is not necessary for all sand particles to be hydrophobic to achieve the behaviour of 100% hydrophobicity.